2022
DOI: 10.3390/insects13050417
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of Peptidoglycan Recognition Proteins OfPGRP-A and OfPGRP-B in Ostrinia furnacalis (Lepidoptera: Crambidae)

Abstract: Peptidoglycan recognition proteins (PGRPs) are important components of insect immune systems, in which they play key roles. We cloned and sequenced two full-length PGRP, named OfPGRP-A and OfPGRP-B, from the Asian corn borer, Ostrinia furnacalis. These two genes comprise open reading frames of 658 and 759 bp, encoding proteins of 192 and 218 amino acids, respectively. qPCR showed that OfPGRP-A and OfPGRP-B are prominently expressed in the midgut of O. furnacalis fourth instar larvae. After inoculation with Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This was further supported when we compared C. bombi to the other conditions, as this time more proteins were down-regulated: C. bombi versus control, 6 down and 2 up; and C. bombi versus Amistar, 10 down and only one up. Furthermore, some proteins of interest have been shown to be involved in response to stimuli and defence mechanisms [ 65 , 66 , 67 , 68 , 69 , 70 ]. As examples, chitinase-like protein (XP_016769017.1 and XP_012237228.1), interferon-related developmental regulator 1-like (XP_017879492.1), heat-shock 70 kDa protein cognate 4 (KMQ87979.1), transferrin-like (XP_035740737.1), apolipophorins, and the two proteins ferritin (ABV68875.1) and vitellogenin (AUX13057.1) that were up-regulated only when Amistar was compared to another condition.…”
Section: Resultsmentioning
confidence: 99%
“…This was further supported when we compared C. bombi to the other conditions, as this time more proteins were down-regulated: C. bombi versus control, 6 down and 2 up; and C. bombi versus Amistar, 10 down and only one up. Furthermore, some proteins of interest have been shown to be involved in response to stimuli and defence mechanisms [ 65 , 66 , 67 , 68 , 69 , 70 ]. As examples, chitinase-like protein (XP_016769017.1 and XP_012237228.1), interferon-related developmental regulator 1-like (XP_017879492.1), heat-shock 70 kDa protein cognate 4 (KMQ87979.1), transferrin-like (XP_035740737.1), apolipophorins, and the two proteins ferritin (ABV68875.1) and vitellogenin (AUX13057.1) that were up-regulated only when Amistar was compared to another condition.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly characterized PRPs are peptidoglycan-recognizing proteins (PGRPs), C-type lectins, scavenger receptor, and apolipophorin III (ApoLp-III) [ 62 , 63 , 64 ]. It is reported that the expression of PGRPs in Plutella xylostella and Ostrinia furnacalis was induced to activate the immune response to Bt [ 65 , 66 ]. The silencing of PxPGRP-S1 by RNA interference (RNAi) significantly reduced the expression of AMP, which caused high mortality under Bt treatment [ 67 ].…”
Section: Immunity Induced By Btmentioning
confidence: 99%
“…They are polymorphonuclear leukocyte-expressed (PGRP1), liver-expressed (PGRP2) or secreted proteins (PGRP3 and PGRP4) (93). Up to 19 PGRPs exist in insects, categorized as short (S) and long (L) variants (153). The short versions are found in hemolymph, cuticle and fatbody cells, while the long forms are mostly expressed in hemocytes (154).…”
Section: Peptidoglycan Recognition Proteinsmentioning
confidence: 99%